Adjustment of dielectric performances for polymer-inorganic composites by ferroelectric filler modification with graphene micro-additive. (2020) - Mjakin, Sergey; Sychov, Maxim; Chekuryaev, Andrey; Sudar, Nikolay
Abstract: The modification of a ferroelectic filler (barium titanate BaTiO3 ) with graphene nanoplates deposited from aqueous dispersions is shown to strongly affect the dielectric performances of composites prepared by the incorporation of thus modified filler into cyanoethyl ester of polyvinyl alcohol (CEPVA) as a polymer binder. The increase of graphene content from 0.2 to 1.6 mg/g results in oscillating changes of permittivity and dielectric losses of the composites, whereas the further increase of the additive amount leads to a steady growth of both performances. The observed effects are found to correlate with specific centers on the filler surface responsible for the filler-binder interaction. The deposited graphene amount is optimized to provide a simultaneous significant increase of dielectric permittivity and decrease of the dielectric loss.